2018
DOI: 10.5194/hess-22-6127-2018
|View full text |Cite
|
Sign up to set email alerts
|

How does initial soil moisture influence the hydrological response? A case study from southern France

Abstract: Abstract. The Cévennes–Vivarais region in southern France is prone to heavy rainfall that can lead to flash floods which are one of the most hazardous natural risks in Europe. The results of numerous studies show that besides rainfall and physical catchment characteristics the catchment's initial soil moisture also impacts the hydrological response to rain events. The aim of this paper is to analyze the relationship between catchment mean initial soil moisture θ̃ini and the hydrological response that is quanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 74 publications
(144 reference statements)
3
20
0
Order By: Relevance
“…While much work has been done to estimate future climatic conditions, changes in hydrological variables, including surface conditions, can also strongly modulate climatic trends (Knighton et al, 2017). In particular, it is known that in many catchments the initial soil moisture conditions prior to flood events play a key role in flood generation (Brocca et al, 2008;Tramblay et al, 2010;Raynaud et al, 2015;Woldemeskel and Sharma, 2016;Wasko and Sharma, 2017;Uber et al, 2018;Wasko and Nathan, 2019), and its temporal change has not been much analyzed up to now. Between two episodes of rain, the base flow of the perennial rivers originates from the draining of the water contained in the soils and for some basins from the aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…While much work has been done to estimate future climatic conditions, changes in hydrological variables, including surface conditions, can also strongly modulate climatic trends (Knighton et al, 2017). In particular, it is known that in many catchments the initial soil moisture conditions prior to flood events play a key role in flood generation (Brocca et al, 2008;Tramblay et al, 2010;Raynaud et al, 2015;Woldemeskel and Sharma, 2016;Wasko and Sharma, 2017;Uber et al, 2018;Wasko and Nathan, 2019), and its temporal change has not been much analyzed up to now. Between two episodes of rain, the base flow of the perennial rivers originates from the draining of the water contained in the soils and for some basins from the aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Though the total values of rainfall of the Event VI and VII were similar (104.59 mm and 139.12 mm, respectively), the values of the initial soil water content were slightly different (0.55 cm 3 /cm 3 in Event VI and 0.41 cm 3 /cm 3 in Event VII), which might result in the differences in the peak flow between these events (0.15mm in Event VI and 0.09mm in Event VII). Zehe et al (2007) and Uber et al (2018) found significant effects of initial soil moisture condition on discharge values.…”
Section: Linear Correlation Of Soil-moisture Spatial Distribution Witmentioning
confidence: 93%
“…In hydrology, soil moisture is the key component for the partitioning of rainfall into evapotranspiration, infiltration and runoff (Vereecken et al, 2008;Brocca et al, 2017;Rajib et al, 2016;Fuamba et al, 2019). In particular, the antecedent soil moisture condition of a catchment is among one of the most important factors for flood triggering (Uber et al, 2018;Zhuo and Han, 2017). For hydrological modelling, soil moisture is a vital state variable.…”
Section: Introductionmentioning
confidence: 99%